Manajemen dan Peran Bursa Kerja Khusus dalam Pengenalan dan Pengembangan Karier Siswa di SMKN 2 Jiwan - Hidayati, Khusnul (Indonesian Journal of Learning and Instructional Innovation, 2023)
This research aims to provide a detailed description of the Special Job Market (BKK) management in facilitating the placement of vocational high school (SMK) graduates into the workforce.The approach used in this research is a qualitative descriptive approach.The study was conducted at SMKN 2 Jiwan, Madiun Regency. Data were collected through a series of methods,including interviews, observations, and document analysis.The management of the Special Job Market (BKK) at SMKN 2 Jiwan is carried out in four stages: planning, organizing, implementing, and controlling.In the planning stage, the steps taken include surveys of relevant business and industry partners, coordination meetings with the BKK team, the signing of a Memorandum of Understanding between the vocational school (SMK) and business partners, as well as the implementation of career guidance and alumni tracking.The organizing stage involves the coordination of BKK administrators in collaboration with the Vice Principal for Public Relations.The implementation stage encompasses the signing of the MoU,the execution of workforce recruitment processes, career guidance related to recruitment, and the execution of alumni tracking (tracer istudy).The final stage is controlling, involving monitoring and auditing, both internally and externally. The results of the control demonstrate that the BKK has been operating optimally, although there are still some aspects that need improvement for future programs. Penelitian ini bertujuan untuk memberikan deskripsi terperinci mengenai manajemen Bursa Kerja Khusus (BKK) dalam memfasilitasi penyaluran lulusan SMK ke dunia kerja. Pendekatan yang digunakan dalam penelitian ni adalah pendekatan deskriptif kualitatif. Penelitian ini dilakukan di SMKN 2 Jiwan, Kabupaten Madiun. Data dikumpulkan melalui serangkaian metode, termasuk wawancara, observasi, serta analisis dokumen. Manajemen Bursa Kerja Khusus (BKK) di SMKN 2 Jiwan dijalankan melalui empat tahapan: merencanakan, mengorganisasikan, melaksanakan,dan mengendalikan.Pada tahap merencanakan, langkah-langkah yang dilakukan yaitu survei terhadap berbagai IDUKA yang relevan,rapat koordinasi dengan tim BKK, penandatanganan Memorandum of Understanding antara SMK dan IDUKA, serta pelaksanaan pembimbingan karir dan penelusuran lulusan.Tahap pengorganisasian melibatkan pengurus BKK dengan berkoordinasi Wakil Kepala Sekolah Bidang Humas.Tahap melaksanakan mencakup penandatanganan MoU, pelaksanaan proses rekrutmen tenaga kerja, bimbingan karir terkait rekrutmen,dan pelaksanaan penelusuran lulusan (tracer study).Tahap akhir adalah mengendalikan, mengawasi dan mengaudit, baik secara nternal maupun eksternal. Hasil dari penelitian adalah manajemen BKK SMKN 2 Jiwan berjalan dengan optimal meskipun masih ada beberapa aspek yang perlu ditingkatan untuk program-program